Determinants of information seeking and preventive behavior for perinatal depression among chinese pregnant women: an extension of the risp model - Li, Miaomiao; Abas, Wan Anita Wan; Ma'rof, Aini Azeqa (Elsevier, 2026)
Perinatal depression (PND) poses a growing health risk for pregnant women in China, yet research on their information-seeking and preventive intention remains limited. This study investigates the primary determinants shaping Chinese pregnant women's engagement in seeking information about PND and its prevention. A structured 41-item questionnaire was administered in Guangzhou through a cross-sectional survey design, yielding 406 valid responses. The findings identified five significant predictors of health information seeking intention: risk perception, affective responses, information insufficiency, informational subjective norms, and attitude, with attitude being the strongest predictor. Relevant channel beliefs moderated the relationship between information insufficiency and health information seeking intention, whereas perceived information-gathering capacity showed no significant moderating effect. Additionally, health information seeking intention was found to positively influence preventive intention. This study is pioneering in its application of the RISP model to the field of perinatal depression, thereby expanding its theoretical scope. By extending the model's pathways, the study offers key empirical evidence demonstrating how information seeking intention can facilitate the formation of preventive intention. It is recommended that policymakers develop an intervention framework for perinatal depression that centers on informational empowerment.